Getting Excited About Public Speaking: A Replication - Poynter Michelle; Pasqualini Marcia Smith (Psychology of Language and Communication)
Can three little words improve a person’s public speaking performance? Brooks (2014, Study 2) predicted and found that college students who were instructed to say aloud “I am excited” before delivering a stressful 2-3 min speech reported feeling more excited but not less anxious, compared to participants who were instructed to say “I am calm.” As Brooks also predicted, independent judges rated the performance of the “excited” group as better than the “calm” group across four indices (persuasive, competent, confident, persistent), and the “excited” group had longer speech duration. In a direct replication and extension, we found nearly identical results for self-report, but no differences between conditions on any observer ratings of performance, nor on an additional indirect measure of anxiety (Emotional Stroop). We discuss why this minimal reappraisal intervention affected self-report but did not result in observable improvements in public speaking.